Islamic Education Directives for the Prevention of Epidemics- Corona Model- and the Reduction and Enhancement of Their Effects in the Educational Curricula of the Hashemite Kingdom of Jordan - Jarrah, Khawla Akram (Journal of Educational and Psychological Sciences, 2022)
The aim of the research is to clarify the directives of Islamic education for the concerned authorities and societies; to combat the Covid- 19 virus epidemic, the researcher used the inductive approach and the documentary survey descriptive approach. The sample consisted of a group of selected texts from sources, jurisprudence books, and recent studies on epidemics and infectious diseases. Where the first topic dealt with the definition of the concepts and terms of research, and the second topic dealt with the directives of Islamic education to combat epidemics and reduce their effects. A conclusion; It included the most important results, recommendations and suggestions. Among the most important findings of the researcher: the greatness of Islamic education, as it preceded scientific discoveries in explaining preventive measures against infectious diseases, and the lack of Islamic guidelines in school curricula that would educate young people to limit the spread of epidemics. Based on the results, the researcher recommended applying the instructions of Islamic education in all areas of life, and setting strict laws to limit the spread of epidemics, taking into account the prevention and treatment of various diseases.
Keywords: Corona pandemic; Islamic education; preventive measures; epidemics